Policing the Police: Northern Ireland's Marching Season
Co-produced by the WITNESS Project of the Lawyers Committee for Human Rights and the Committee on the Administration of Justice (CAJ), Belfast, Northern Ireland, POLICING THE POLICE looks at the human rights issues surrounding the policing of parades of the majority unionist community during the 1995-1997 marching seasons. A small number of these marches pass through minority Republican communities. Many nationalists consider the parades "triumphalist" and have called for them to be re-routed. POLICING THE POLICE features footage of the policing of the parades and interviews with human rights workers and local residents.